Mid‐infrared polarisation rotator based on an asymmetric Ge‐strip‐on‐si waveguide. Issue 6 (1st December 2014) - He, Wenbin; Cassan, Eric
Abstract : Polarisation rotators are of great importance for high‐data rate integrated photonic circuits. In this study, the authors provide the design of a polarisation rotator based on an asymmetric germanium strip on a silicon substrate operating in the mid‐infrared band which has recently received a strong interest because of its huge potential for various applications. Two different asymmetric geometries, the slant and the two‐step waveguides, are presented and theoretically investigated. Both of them can achieve single‐mode transmission and high conversion efficiency (> 90%) in short polarisation rotation lengths (−60 µm or −10 λ and −120 µm or −20 λ ) and wide operation bandwidth (−5 µm ≤ λ ≤ −7 μm). The optimisation process and spectral analysis are provided and the properties of these two geometries are compared.